Peran Gaya Hidup Sehat dalam Mengendalikan Tekanan Darah pada Pasien Hipertensi - Ines da Luz Correia Barros; Abdul Wahid (Jurnal Pengabdian Ilmu Kesehatan, 2026)
Hypertension is a significant public health issue that continues to rise both globally and in Indonesia, particularly among the productive adult population. This study aims to analyze the role of a healthy lifestyle in controlling blood pressure among hypertensive patients through a literature review by examining recent national studies on diet, physical activity, stress management, and medication adherence. The analysis indicates that implementing a balanced diet, engaging in regular exercise, managing stress, and adhering to prescribed therapy have a significant impact on lowering blood pressure and improving patients’ quality of life. Nursing interventions based on education, counseling, and continuous monitoring have proven effective in encouraging patients to maintain healthy lifestyle practices consistently. These findings emphasize the crucial role of nurses in hypertension management through a holistic approach involving patients, families, and communities, supporting strategies for long-term complication prevention.